Four hundred souls eaudiobook A community history of african america, 1619-2019. - Kendi, Ibram X. (Random House Audio, 2021)
A chorus of extraordinary voices comes together to tell one of history’s great epics: the four-hundred-year journey of African Americans from 1619 to the present—edited by Ibram X. Kendi, author of  How to Be an Antiracist,  and Keisha N. Blain, author of  Set the World on Fire . The story begins in 1619—a year before the Mayflower —when the White Lion disgorges “some 20-and-odd Negroes” onto the shores of Virginia, inaugurating the African presence in what would become the United States. It takes us to the present, when African Americans, descendants of those on the White Lion and a thousand other routes to this country, continue a journey defined by inhuman oppression, visionary struggles, stunning achievements, and millions of ordinary lives passing through extraordinary history.  Four Hundred Souls is a unique one-volume “community” history of African Americans. The editors, Ibram X. Kendi and Keisha N. Blain, have assembled ninety brilliant writers, each of whom takes on a five-year period of that four-hundred-year span. The writers explore their periods through a variety of techniques: historical essays, short stories, personal vignettes, and fiery polemics. They approach history from various perspectives: through the eyes of towering historical icons or the untold stories of ordinary people; through places, laws, and objects. While themes of resistance and struggle, of hope and reinvention, course through the book, this collection of diverse pieces from ninety different minds, reflecting ninety different perspectives, fundamentally deconstructs the idea that Africans in America are a monolith—instead it unlocks the startling range of experiences and ideas that have always existed within the community of Blackness.  This is a history that illuminates our past and gives us new ways of thinking about our future, written by the most vital and essential voices of our present.  Read by a full cast, including: Joniece Abbott-Pratt, Amir Abdullah, Ryan Vincent Anderson, Kristen Ariza, Dashawn Barnes, Joshua Bennett, Quincy Tyler Bernstine, Andre Blake, Torian Brackett, Donte Bonner, Mahogany L. Browne, Ron Butler, Kellie Carter-Jackson, Brianna Collette, Karen Chilton, Sean Crisden, Keith David, Angela Y. Davis, William DeMeritt, Leonard Dozier, Robin Eller, Kevin R. Free, James Fouhey, Alicia Garza, Dion Graham, Danai Gurira, Jerome Harmann-Hardeman, Jamal Henderson, Ethan Herisse, Susan Heyward, Cary Hite, Dominic Hoffman, Sherrilyn Ifill, James Monroe Iglehart, JD Jackson, Zainab Jah, Nikole Hannah-Jones, Sullivan Jones, Peter Francis James, Terrence Kidd, January LaVoy, Adam Lazarre-White, Keylor Leigh, Nicole Lewis, Dennis Logan, Chante McCormick, Desmond Manny, Jesus Martinez, Heather McGhee, Sheryl Mebane, Robin Miles, Karen Murray, Soneela Nankani, Leon Nixon, Soledad O’Brien, Leslie Odom, Jr., Adenrele Ojo, Genesis Oliver, Prentice Onayemi, Tovah Ott, Morgan Parker, Imani Parks, Lisa Renee Pitts, Imani Jade Powers, Rhett Samuel Price, Bill Quinn, Phylicia Rashad, David Sadzin, Joshua David Scarlett, Heather Alicia Simms, Shayna Small, Patricia Smith, Marisha Tapera, Tashi Thomas, Damian Thompson, TL Thompson, Ella Turenne, Bahni Turpin, Anita Welch, Jade Wheeler, Samira Wiley, Zenzi Williams, Mirron Willis, Andia Winslow, Kai Wright, and with co-editors Ibram X. Kendi and Keisha N. Blain